The Agricultural Impact of IFAD Intervention in Crop Production in Semi Arid Zone in Um Rowaba and Bara localities of North Kordofan State, Sudan - E.Maruod, Maruod; Gaafar B. Suliman; Elzubair E. Elzain; Attika M. E.Marouf; Mohammed Y. Abdalla, (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2019)
The current study was conducted in April 2009, in Um Rowaba and Bara localities to assess the impact of IFAD project in socio- economic interventions  in rural communities, livelihood. The study used field survey household questionnaire to collect primary data, stratified systematic random sampling technique was used. 384 households was the sample interviewed. Results showed that 14.6% of the respondents received agricultural inputs in form of improved seeds in very miner quantities, 85.5% of the respondents did not receive any kind of agricultural inputs during the project intervention, 28.1% of the respondents  of both males and females said that the farmers field schools (FFS) were established in the project area, to disseminate the extension packages among the farmers, 71.9%of participants in (FFS) responded negative disseminate of extension packages among them. 75.9 % of the respondents indicated that there was no increased in agricultural production during the project interventions in the study area. To increase the agricultural production in the project area more attention should be given to agricultural extension services, capacity building, and more studies to be conducted in IFAD (North Kordofan Rural Development) NKRDP to improve its performance in alleviating poverty and ensuring food security in the project area.